Periódico Psicologia da Educação: produção científica em 20 anos de existência - Silva, José Gilberto de Andrade (2018)
This research aimed to investigate the scientific production of the 20 years of publication of the journal Psicologia da Educação, linked to the Program of Postgraduate Studies in Education, area of concentration: Psychology of Education. 294 articles published from 1995 to 2015 were analyzed. For the analysis were used bibliometric and the software ALCESTE. The results showed that the Journal has been improving its publications, despite the need to observe some points. Results indicated that the psychological approaches are the most used theoretical bases; in addition, the school context is the most chosen place for the execution of the studies, being the childhood educational the level preferred. Survey of methodological procedures indicated that a large part of the research published by the journal and the most used data collections are for the collection of documents or through interviews. The titles and keywords indicated as topics of greater interest those related to the school context, such as: formation of teachers, teaching and learning, school culture, the most studied themes, besides the history and contributions of Education Psychology to education. Related to the results of other researches, here was observed predominance of psychological theories in the understanding of educational phenomena. It hoped that study contributes to this Program and to the editors of this Journal